DEVELOPMENT OF PRE-SERVICE MATHEMATICS TEACHERS’ SOFT SKILLS STUDYING THE TOPIC "DIOPHANTINE EQUATIONS" - Lukashova, Tetіana; Drushlyak, Marina; Khvorostina, Yurii (Physical and Mathematical Education, 2022)
Formulation of the problem. In today's world, employers pay attention to the qualities of the future – soft skills ("System Four Cs» – Collaboration, Communication, Creativity, Critical thinking), which a future competitive specialist, especially a teacher, must have, since this is a profession in which soft skills and hard skills play an equal role.Materials and methods. System analysis of scientific, educational, and methodical literature; comparison and synthesis of theoretical positions; generalization of own pedagogical experience.Results. The results of the study highlight possible ways to solve the problem of developing of pre-service mathematics teachers’ soft skills on the example of studying the topic "Diophantine Equations" in the course "Olympic Mathematics" of the educational program “Secondary Education (Mathematics. Computer Science)” of the second (master's) level of higher education at Makarenko Sumy State Pedagogical University. Without pretending to be complete, the authors highlight the ten most common methods of solving Diophantine equations, each of which is illustrated by relevant examples with detailed explanations.Conclusions. During the study of the topic, such soft skills as creativity (the ability to apply heuristic techniques; the ability to use the acquired knowledge in non-standard situations; the ability to generate solution ideas); logical thinking; critical thinking (determining the type of Diophantine equation and the rational choice of one or another method of solving it, the ability to "see the highlight" that gives the key to the solution; the ability to ask constructive questions during the collective solving of equations in classes, analyze, argue and evaluate ideas and solutions); communication (the ability to defend one's point of view, to argue why a specific method is chosen, why other methods are not suitable for solving a given type of Diophantine equation); time management skills when setting deadlines for completing homework, individual tasks, etc., the ability to rationally allocate your time; the ability to learn, since most of the time of the educational component is devoted to independent study, are developed.
Keywords: soft skills; pre-service mathematics teachers; Diophantine equations; methods of solving Diophantine equations